Comparative Transcriptome Analysis of Two Types of Rye Under Low-Temperature Stress - Haonan Li; Jiahuan Zhao; Weiyong Zhang; Ting He; Dexu Meng; Yue Lu; Shuge Zhou; Xiaoping Wang; Haibin Zhao (Current Issues in Molecular Biology)
Wheat is a crucial food crop, and low-temperature stress can severely disrupt its growth and development, ultimately leading to a substantial reduction in wheat yield. Understanding the cold-resistant genes of wheat and their action pathways is essential for revealing the cold-resistance mechanism of wheat, enhancing its yield and quality in low-temperature environments, and ensuring global food security. Rye (Secale cereale L.), on the other hand, has excellent cold resistance in comparison to some other crops. By studying the differential responses of different rye varieties to low-temperature stress at the transcriptome level, we aim to identify key genes and regulatory mechanisms related to cold tolerance. This knowledge can not only deepen our understanding of the molecular basis of rye’s cold resistance but also provide valuable insights for improving the cold tolerance of other crops through genetic breeding strategies. In this study, young leaves of two rye varieties, namely “winter” rye and “victory” rye, were used as experimental materials. Leaf samples of both types were treated at 4 °C for 0, 6, 24, and 72 h and then underwent RNA-sequencing. A total of 144,371 Unigenes were reconstituted. The Unigenes annotated in the NR, GO, KEGG, and KOG databases accounted for 79.39%, 55.98%, 59.90%, and 56.28%, respectively. A total of 3013 Unigenes were annotated as transcription factors (TFs), mainly belonging to the MYB family and the bHLH family. A total of 122,065 differentially expressed genes (DEGs) were identified and annotated in the GO pathways and KEGG pathways. For DEG analysis, 0 h 4 °C treated samples were controls. With strict criteria (p < 0.05, fold-change > 2 or <0.5, |log2(fold-change)| > 1), 122,065 DEGs were identified and annotated in GO and KEGG pathways. Among them, the “Chloroplast thylakoid membrane” and “Chloroplast” pathways were enriched in both the “winter” rye and “victory” rye groups treated with low temperatures, but the degrees of significance were different. Compared with “victory” rye, “winter” rye has more annotated pathways such as the “hydrogen catabolic process”. Although the presence of more pathways does not directly prove a more extensive cold-resistant mechanism, these pathways are likely associated with cold tolerance. Our subsequent analysis of gene expression patterns within these pathways, as well as their relationships with known cold-resistance-related genes, suggests that they play important roles in “winter” rye’s response to low-temperature stress. For example, genes in the “hydrogen catabolic process” pathway may be involved in regulating cellular redox balance, which is crucial for maintaining cell function under cold stress.